2006
DOI: 10.1177/107110070602700305
|View full text |Cite
|
Sign up to set email alerts
|

Extensor Hallucis Capsularis: Frequency and Identification on MRI

Abstract: Up to 14% of the population may have an EHC tendon suitable for grafting in reconstructive surgeries, particularly surgeries related to hallux dysfunction. MRI may have a role in the preoperative identification of the EHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 6 publications
3
17
0
2
Order By: Relevance
“…Also, it was always thinner than the main EHL tendon. This pattern of origin was consistent with the report of Boyd et al (2006) in that the AT may diverge from either EHL tendon or the muscle belly in adults. However, different from ours, Boyd stated that AT may also arise from several other muscles such as anterior tibial and extensor hallucis brevis muscles.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Also, it was always thinner than the main EHL tendon. This pattern of origin was consistent with the report of Boyd et al (2006) in that the AT may diverge from either EHL tendon or the muscle belly in adults. However, different from ours, Boyd stated that AT may also arise from several other muscles such as anterior tibial and extensor hallucis brevis muscles.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, Bibbo et al (2004) reported that their findings did not support the hypothesis that the accessory tendon of the first MTPJ plays role in the development of hallux valgus. Tate et al (cited in Bibbo et al, 2004 andBoyd et al, 2006) described the function of AT of EHL muscle as the stabilization of the first MTPJ capsule (by preventing capsular buckling or impingement) upon dorsiflexion of the hallux. Because of the absence of AT in~20% of the specimens and its small size, Bibbo et al (2004) questioned this function of AT.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fibras carnosas en los dos cuartos medios de la cara cara medial del peroné colocada por delante de la cresta interósea; porción adyacente de la membrana interósea de la pierna y fascia de la pierna, en la parte vecina de dicha membrana 5,6,7,8,9,10,11,12,13,14,15,16 .…”
Section: Origenunclassified